A dependência de drogas como um problema de identidade: possibilidades de apresentação do 'eu' por meio da oficina terapêutica de teatro - Lima, Aluísio Ferreira de (2005)
This dissertation aims to investigate the mean of the therapeutic workshop of theater to the person who has been treated by the ambulatory of drug dependency in the city of Diadema SP. To do so, we start from the Social Psychology and the concept of Identity as the central category of analysis, considering to understand not only the phenomenon in its instrumental aspect, but, all the context in which the individual that uses psychoactive substances is inserted, in the tradition vs. modernity conflicts, of the market of consumption, of the diagnostic and treatments; with the proposal to present a contribution in such a way theoretical as political. The research was carried through from the narrative of the participant life history, which was recorded and transcript with the consent of the interviewed. While analyzing the life history narrative, we focused on happenings immediately before, during and after the participation on the therapeutic workshop of theater, asking the participant to tell several aspects of his life and not only the one who made the person search for drug dependency treatment. What has changed in his family, social, professional and individual life, observing how has this process developed. The dissertation is divided in five chapters that approach several aspects in which the individuals who use psychoactive substances are inserted. In this way, this work weaves some reflections on the question of drug usage and the possibility of change through the therapeutic workshop of theater, as well as it offers subsidy to discuss the Post Conventional Identities (Habermas) and the possibilities of emancipation in Modernity.